2020
DOI: 10.1177/2048872619900095
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind pilot trial comparing a mean arterial pressure target of 65 mm Hg versus 72 mm Hg after out-of-hospital cardiac arrest

Abstract: Background: After resuscitation from out-of-hospital cardiac arrest, mean arterial pressure below 65 mm Hg is avoided with vasopressors. A higher blood-pressure target could potentially improve outcome. The aim of this pilot trial was to investigate the effect of a higher mean arterial pressure target on biomarkers of organ injury. Methods: This was a single-centre, double-blind trial of 50 consecutive, comatose out-of-hospital cardiac arrest patients randomly assigned in a 1:1 ratio to a mean arterial pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 34 publications
1
58
0
Order By: Relevance
“…Among these full studies, ve were excluded for unavailable data, four were excluded because they were studies, and three were excluded due to duplication of data. Finally, nine studies [4][5][6][7][8][9][10][11][12] were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among these full studies, ve were excluded for unavailable data, four were excluded because they were studies, and three were excluded due to duplication of data. Finally, nine studies [4][5][6][7][8][9][10][11][12] were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies [4][5][6][7][8][9][10][11][12] are outlined in Table 1. The mean age ranged from 58 years to 63 years, the proportion of male subject varied from 58-88%, and the duration of MAP target was between 2 and 96 h. Four studies [9][10][11][12] were conducted in North America, three [4,6,8] in Europe, and two in Asia [5]. The risk of bias assessment for each included study and the summative assessment by domain are shown in Supplementary Tables 1 and 2.…”
Section: Characteristics Of the Included Studies And Quality Assessmentmentioning
confidence: 99%
See 3 more Smart Citations